Weed management strategies in organic farming - Mishra, J. S. (Indian Farming, 2025)
Weeds pose a significant challenge to organic farming due to the absence of herbicides, leading to substantial crop losses. Effective weed management in organic farming should focus on reducing weed populations to manageable levels without attempting complete elimination. Strategies like cultural practices, including the stale seed-bed technique, soil solarization, and crop diversification,are essential. Manual, mechanical, and biological control methods play key roles in maintaining crop-weed competition balance. Integrated Weed Management (IWM), involving prevention, mechanical tools, and ecological practices, offers a sustainable and environment-friendly approach, promoting soil health and enhancing crop productivity.